Pewnym Rozwiązaniu w Teorii Zginania Płyt Cienkich o Ortotropii Cylindrycznej - Barański, W. (Engineering Transactions, 1964)
This is an analysis of the general solution of the homogeneous equation of plate deflection obtained by SEN GUPTA. The influence of the material parameters on the form of the solution and the singularities of the internal forces at the centre of the plate is discussed. The results are illustrated by a graph (Fig. 1). A particular solution of the plate equation is obtained in the case in which the load can be represented in the form of a series ∑_npn (r) cos⁡nθ. This is done by the method of variation of the integration constants.